2021
DOI: 10.1111/nmo.14178
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution impedance manometry characterizes the functional role of distal colonic motility in gas transit

Abstract: The transit of intraluminal contents in the colon is governed by the action of colonic smooth muscle. Using concurrent manometry and imaging techniques, a number of previous studies have attempted to relate the movements of liquid and solid luminal content with specific patterns of motor activity. [1][2][3][4][5][6][7] However, the colonic motor patterns associated with gas transit have not been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Dinning et al [ 24 ] applied HRCM to characterise a substantial postprandial increase in the retrograde cyclic motor pattern in the distal colon as a feature of a healthy meal response, and Lin et al [ 20 ] subsequently localised this activity to be maximal in the same rectosigmoid region as the “functional sphincter”. Using another modality, high‐resolution impedance manometry has shown gas insufflation of the sigmoid colon initiates retrograde cyclic motor patterns to limit gas transit to the rectum [ 35 ]. These studies extended the earlier work of Rao and Welcher, who proposed periodic rectal motor activity served as an “intrinsic braking mechanism that prevents the untimely flow of contents” [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dinning et al [ 24 ] applied HRCM to characterise a substantial postprandial increase in the retrograde cyclic motor pattern in the distal colon as a feature of a healthy meal response, and Lin et al [ 20 ] subsequently localised this activity to be maximal in the same rectosigmoid region as the “functional sphincter”. Using another modality, high‐resolution impedance manometry has shown gas insufflation of the sigmoid colon initiates retrograde cyclic motor patterns to limit gas transit to the rectum [ 35 ]. These studies extended the earlier work of Rao and Welcher, who proposed periodic rectal motor activity served as an “intrinsic braking mechanism that prevents the untimely flow of contents” [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long‐distance retrograde reflexes are a key mechanism in the physiologic feedback control of gut function, regulating gastric tone, gastric emptying, upper small bowel phasic activity and intestinal tone 13–16 . It has been shown that experimental colonic distension in humans elicits propagated contractions via a local, peristaltic reflex directly mediated by the enteric nervous system 17–20 . Colonic stimulation also elicits long‐distance reflexes modulating the activity of other areas of the gut 21 .…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] It has been shown that experimental colonic distension in humans elicits propagated contractions via a local, peristaltic reflex directly mediated by the enteric nervous system. [17][18][19][20] Colonic stimulation also elicits long-distance reflexes modulating the activity of other areas of the gut. 21 A recent study in a canine model showed that distension of the colon inhibits small bowel contractions via long-distance retrograde inhibitory reflexes.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should examine in detail the impact of ondansetron on left sided colonic motor patterns, particularly examining its impact on retrograde motor patterns as recently described. 56 Alosetron, a potent 5-HT 3 antagonist, stimulates rectosigmoid motility, 16 a paradox which could be resolved if it was proven that it was the retrograde motility that was increased, since this would delay transit of both liquid and gas colonic content and inhibit defecation.…”
Section: Ta B L Ementioning
confidence: 99%